Soccer athletes are superior to non-athletes at perceiving soccer-specific and non-sport specific human biological motion - Romeas, Thomas; Faubert, Jocelyn (Frontiers in Psychology, 2015)
Recent studies have shown that athletes’ domain specific perceptual-cognitive expertise can transfer to everyday tasks. Here we assessed the perceptual-cognitive expertise of athletes and non-athletes using sport specific and non-sport specific biological motion perception tasks. Using a virtual environment, university-level soccer players and university students’ non-athletes were asked to perceive the direction of a point-light walker and to predict the trajectory of a masked-ball during a point-light soccer kick. Angles of presentation were varied for orientation (upright, inverted) and distance (2m, 4m, 16m). Accuracy and reaction time were measured to assess observers’ performance. The results highlighted athletes’ superior ability compared to non-athletes to accurately predict the trajectory of a masked soccer ball presented at 2m (reaction time), 4m (accuracy and reaction time) and 16m (accuracy) of distance. More interestingly, experts also displayed greater performance compared to non-athletes throughout the more fundamental and general point-light walker direction task presented at 2m (reaction time), 4m (accuracy and reaction time) and 16m (reaction time) of distance. In addition, athletes showed a better performance throughout inverted conditions in the walker (reaction time) and soccer kick (accuracy and reaction time) tasks. This implies that during human biological motion perception, athletes demonstrate an advantage for recognizing body kinematics that goes beyond sport specific actions.